2020
DOI: 10.1101/2020.04.13.20063099
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of psychological distress and demand induced by COVID-19 during the lockdown period in patients undergoing peritoneal dialysis and hemodialysis: a cross-section study in a tertiary hospital

Abstract: Background:Since the outbreak of COVID-19 in December 2019, it has spread rapidly and widely,

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Need of a nephrologyconsultation to facilitate disease self-management during the pandemic and difficulty adjusting to the contingency plans adopted by dialysis units were also mentioned. Overall, these findings are congruent with the results of the only study that evaluated the experience of patients with ESRD with COVID-19 in China, suggesting that patients undergoing in-center HD have high levels of distress during the confinement period 16. Although there are still few studies examining the negative psychosocial impacts of COVID-19 in non-COVID-19 patients, there are even fewer focusing on positive outcomes 38.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Need of a nephrologyconsultation to facilitate disease self-management during the pandemic and difficulty adjusting to the contingency plans adopted by dialysis units were also mentioned. Overall, these findings are congruent with the results of the only study that evaluated the experience of patients with ESRD with COVID-19 in China, suggesting that patients undergoing in-center HD have high levels of distress during the confinement period 16. Although there are still few studies examining the negative psychosocial impacts of COVID-19 in non-COVID-19 patients, there are even fewer focusing on positive outcomes 38.…”
supporting
confidence: 77%
“…15 Therefore, COVID-19 is a great challenge for these patients who already have high levels of anxiety and depression under normal circumstances. 16 In addition to renal replacement therapy, patients with ESRD also need to adhere to several disease and treatment-related health behaviors (eg, dietary and fluid restrictions, vascular access care, physical activity, poly-medication protocols, and follow-up consults) that are crucial for survival, 14 but that can be an additional stressful demand to manage during the outbreak.…”
Section: Being On Hemodialysis During the Covid-19 Outbreakmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these factors, CKD patients are more likely to gain negative emotions. A latest study demonstrated that hemodialysis patients had more severe trauma-related stress symptoms than peritoneal dialysis patients ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chinese researchers, based on the observation of patients treated with peritoneal dialysis at home and hemodialysis in a dialysis station, concluded that severe PTSD symptoms appear more often in the group of patients treated with hemodialysis. [13] Home hemodialysis is another effective method to reduce the time spent in the dialysis station. So far, this method is not available in Poland, although it seems that it could be an alternative for patients with contraindications to peritoneal dialysis treatment.…”
Section: Introductionmentioning
confidence: 99%